The Effect of Price and Service Quality on Consumer Purchasing Decisions of Alfamart in Semarang City - Bagus Yunianto Wibowo (International Journal of Education, Vocational and Social Science, 2023)
This study aims to determine and analyse the effect of price and service quality on consumer purchasing decisions. The objectives of this study are: (1) Determine the effect of price on purchasing decisions (2) Determine the effect of service quality on purchasing decisions. By using quantitative descriptive research, the sampling technique used in this research is the saturated sampling method. The data obtained in this study were obtained by distributing questionnaires to 100 respondents of Alfamart consumers in the city of Semarang. SEM Package Amos 24.0 is used as an analytical tool The results obtained are (1) price has a positive and significant effect on purchasing decisions (2) service quality has a positive and significant effect on purchasing decisions.